211k views
4 votes
HELP PLEASE!!!!!!!!!!!

HELP PLEASE!!!!!!!!!!!-example-1
User Terenoth
by
4.9k points

1 Answer

3 votes

Answer:

Part 1)
y=-x^(2) ---> Translated up by 1 units

Part 2)
y=x^(2)+1 ---> Reflected across the x-axis

Part 3)
y=-(x+1)^(2)-1 ---> Translated left by 1 unit

Part 4)
y=-(x-1)^(2)-1 ----> Translated right by 1 unit

Part 5)
y=-x^(2)-1 ----> Reflected across the y-axis

Part 6)
y=-x^(2)-2 ----> Translated down by 1 unit

Explanation:

we know that

The parent function is


y=-x^(2)-1 ----> this is a vertical parabola open downward with vertex at (0,-1)

Calculate each case

Part 1) Translated up by 1 unit

The rule of the translation is

(x,y) -----> (x,y+1)

so

(0,-1) ----> (0,-1+1)

(0,1) ----> (0,0) ----> the new vertex

The new function is equal to


y=-x^(2)

Part 2) Reflected across the x-axis

The rule of the reflection is

(x,y) -----> (x,-y)

so

(0,-1) ----> (0,1) ----> the new vertex

The new function is equal to


y=x^(2)+1

Part 3) Translated left by 1 unit

The rule of the translation is

(x,y) -----> (x-1,y)

so

(0,-1) ----> (0-1,-1)

(0,1) ----> (-1,-1) ----> the new vertex

The new function is equal to


y=-(x+1)^(2)-1

Part 4) Translated right by 1 unit

The rule of the translation is

(x,y) -----> (x+1,y)

so

(0,-1) ----> (0+1,-1)

(0,1) ----> (1,-1) ----> the new vertex

The new function is equal to


y=-(x-1)^(2)-1

Part 5) Reflected across the y-axis

The rule of the reflection is

(x,y) -----> (-x,y)

so

(0,-1) ----> (0,-1) ----> the new vertex

The new function is equal to


y=-x^(2)-1

Part 6) Translated down by 1 unit

The rule of the translation is

(x,y) -----> (x,y-1)

so

(0,-1) ----> (0,-1-1)

(0,1) ----> (0,-2) ----> the new vertex

The new function is equal to


y=-x^(2)-2

HELP PLEASE!!!!!!!!!!!-example-1
User Rohin Sidharth
by
4.2k points